Integrating Entrepreneurial Values into Faith-Based Education: A Study of Traditional Pesantren in Aceh - Abubakar, Abubakar; Maifizar, Arfriani; Fajri, Heri; Basri, Basri; Arif, Arifudin M.; Saputra, Nanda (SCAD Independent, 2025)
This study explores the integration of entrepreneurial values within the educational practices of traditional pesantren in Aceh, Indonesia. While entrepreneurship is not formally taught, pesantren foster entrepreneurial competencies through religious devotion, moral education, and communal life. Using a qualitative approach, data were collected through semi-structured interviews, participant observation, and document analysis. The findings reveal that pesantren cultivate dual dimensions of edupreneurship: batiniyah values such as sincerity, perseverance, and reliance on God, and lahiriyah practices, including community leadership, social responsibility, and trust-building. These values emerge organically from daily religious practices and form a moral foundation for entrepreneurial engagement. Despite challenges such as the absence of formal entrepreneurial curricula and limited critical thinking development, pesantren demonstrates a sustainable model of faith-based entrepreneurship that balances religious commitment with economic agency. This study contributes to global discussions on Islamic education and value-based entrepreneurship, offering a context-specific paradigm for integrating ethical economic empowerment into religious education systems. The Acehnese pesantren experience provides a valuable alternative to secular models, emphasizing indigenous educational traditions’ potential to drive spiritual and socioeconomic transformation.